2009
DOI: 10.1038/hdy.2009.149
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale SNP genotyping in crosses between outbred lines: how useful is it?

Abstract: Although genome-wide association (GWA) studies are not worth the effort in crosses between inbred lines, many crosses are actually made up of divergent yet outbred populations. Despite its relevance, however, this experimental setting has not been studied at a time when SNP microarrays are available in many species. To assess whether GWA can be useful in this setting, we performed combined coalescence-gene dropping simulations. We studied the influence of marker density, QTL effect and QTL allele frequency on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…The genotypes of 932 F 2 animals were simulated using gene-dropping [38] theory, by conditioning on a real pedigree and on the haplotypes of the 55 F 1 parents (6 males and 49 females) from the real F 2 population. The haplotypes were estimated at a high accuracy from the genotypes of the F 1 parents and 19 F 0 ancestors (4 Duroc boars and 15 Pietrain sows), using the software MERLIN [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes of 932 F 2 animals were simulated using gene-dropping [38] theory, by conditioning on a real pedigree and on the haplotypes of the 55 F 1 parents (6 males and 49 females) from the real F 2 population. The haplotypes were estimated at a high accuracy from the genotypes of the F 1 parents and 19 F 0 ancestors (4 Duroc boars and 15 Pietrain sows), using the software MERLIN [39].…”
Section: Methodsmentioning
confidence: 99%
“…As an example, there were 1,405 SNP on chromosome 12 that were spread over 64.2 Mb, and the ensuing average distance between markers was 0.04573 Mb. By assuming a recombination rate of 1 cM per Mb [38], the number of recombinations in chromosome 12 was drawn from a Poisson distribution with parameter equal to 64.2 / 100 = 0.642. The next step was to assign the resulting gametes carrying these recombinations of the F 1 genotypes to their F 2 progeny.…”
Section: Methodsmentioning
confidence: 99%
“…For an F 2 population, the power of detecting QTLs could reach 0.90 when the sample size is 500 and the heritability exceeds 0.04 (Satagopan et al, 2007). If the heritability reaches 0.18, the power of detecting QTLs would be close to one in an F 2 population including 200 individuals from two outbred lines crossing by 50 k SNP panels (Ledur et al, 2010). In fact, the heritability of body weight is generally no more than 0.25 in chickens (Wolc et al, 2009;Chen et al, 2011); however, many studies have successfully detected QTLs for body weights by GWAS (Gu et al, 2011;Xie et al, 2012).…”
Section: Population Structurementioning
confidence: 99%
“…The currently available chicken 60 k SNP panel provides genome coverage and map resolution unavailable from microsatellite markers and has the potential of much improved accuracy in finding the exact QTL locations. A recent study [10] showed that designed populations such as F2 populations for genome-wide association studies (GWAS) were advantageous over random populations in reducing false discovery rate (FDR) and in improving mapping accuracy. In this article, we report results of a genome-wide association analysis of chicken body weight using the chicken 60 k SNP panel in a chicken F2 resource population derived from the cross between Silky Fowl and White Plymouth Rock, which are two chicken breeds with highly divergent phenotypes in growth rate and body weight.…”
Section: Introductionmentioning
confidence: 99%